Bilayer mucoadhesive buccal films with prolonged release of ciclopirox olamine for the treatment of oral candidiasis: In vitro development, ex vivo permeation testing, pharmacokinetic and efficacy study in rabbits - Gajdošová, Markéta; Vetchý, David; Muselík, Jan; Gajdziok, Jan; Juřica, Jan; Vetchá, Martina; Hauptman, Karel; Jekl, Vladimír (International journal of pharmaceutics, 2021)
The incidence of fungal infections has increased in recent decades not only in patients with predisposing and risk factors, but it has also spread up due to the widespread use of broad-spectrum antibiotics, immunosuppressants and corticosteroids. A limited number of drugs are currently used to treat oral candidiasis (OC). There is an emerging need to look for new antifungals, to rework or to explore the already known molecules. Ciclopirox olamine (CPX), a broad-spectrum antifungal agent, is currently used for topical dermatologic treatment. In this study, bilayer mucoadhesive buccal films (MBFs) containing poly(ethylene oxide) (PEO) and Eudragit® NM 30D (EU) with the prolonged release of ciclopirox olamine, were developed for the treatment of oral candidiasis. During ex vivo testing it was found that CPX does not pass through the porcine buccal tissue but it accumulates in it, which may be beneficial for the treatment of candidiasis in the oral cavity. In a pharmacokinetic study, the drug release from mucoadhesive films was prolonged with the maximum plasma concentration at 3.4 (1.4; 5.5) h. All rabbits with stomatitis showed progressive healing after the treatment with CPX bilayer mucoadhesive buccal films without organ pathologies.
Keywords: Animals; Rabbits; Antifungal Agents; ciklopirox; Eudragit; lidé; Pharmacokinetics; Treatment of oral candidiasis; prasata; Mouth Mucosa; Drug Liberation; Mucoadhesive film; orální kandidóza; ústní sliznice; Swine; Ciclopirox; Ciclopirox olamine; Administration, Buccal; aplikace bukální; králíci; zvířata; uvolňování léčiv; Candidiasis, Oral; antifungální látky; Humans